(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
The human gut microbiota is central to maintaining health, influencing immune regulation, metabolic functions, and disease susceptibility. Environmental microbiota—the microbial communities in soil, air, and water—play a crucial role in shaping gut microbiota composition and functionality. However, urbanization, industrialization, and modern lifestyles have significantly reduced exposure to these environmental microbes, leading to diminished microbial diversity and associated health risks. This paper investigates the pathways through which environmental microbial communities interact with human gut microbiota, the implications of urbanization on microbial diversity, and the consequent health outcomes. It highlights key mechanisms linking gut dysbiosis to diseases such as autoimmune disorders, allergies, and metabolic syndromes. Furthermore, it explores interventions, including urban greening, traditional dietary practices, and engineered probiotics, that can mitigate microbial loss. Finally, this paper identifies knowledge gaps and proposes future research directions to enhance our understanding of microbial ecosystems and their role in human health.